2000
DOI: 10.1287/isre.11.1.61.11783
|View full text |Cite
|
Sign up to set email alerts
|

Opening the “Black Box” of Network Externalities in Network Adoption

Abstract: Recent theoretical work suggests that network externalities are a determinant of network adoption. However, few empirical studies have reported the impact of network externalities on the adoption of networks. As a result, little is known about the extent to which network externalities may influence network adoption and diffusion. Using electronic banking as a context and an econometric technique called hazard modeling, this research examines empirically the impact of network externalities and other influences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
125
0
3

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 219 publications
(130 citation statements)
references
References 39 publications
2
125
0
3
Order By: Relevance
“…Extending this stream of research by incorporating the concept of shared networks, Kauffman et al (2000) found support for the network externality hypothesis. …”
Section: Network Effectsmentioning
confidence: 88%
See 1 more Smart Citation
“…Extending this stream of research by incorporating the concept of shared networks, Kauffman et al (2000) found support for the network externality hypothesis. …”
Section: Network Effectsmentioning
confidence: 88%
“…We summarize the limited empirical studies in Table 2. A few studies 7 have examined issues such as the adoption of spreadsheet software (Brynjolfsson and Kemerer 1996) and the diffusion of Bitnet nodes (Gurbaxani 1990), but none have focused on the important role of standards, especially in the context of Internet-based open standards (Kauffman et al 2000).…”
Section: Network Effectsmentioning
confidence: 99%
“…Network externalities are the effects on a product user of other users consuming the same product, thereby expanding the analysis of adoption and diffusion beyond individual firms to the surrounding network of firms. Specifically, Kauffman, McAndrews, and Wang (2000) examine the impacts of several network variables on elapsed time for banks to adopt a shared ATM network. They find that the size of an individual bank's network increases the time for the network to adopt the shared IOS.…”
Section: Robey Et Al/interorganizational Systemsmentioning
confidence: 99%
“…Gandal (1994) and Brynjolfsson and Kemerer (1996) show that, other things being equal, users are willing to pay a premium for compatibility and goods with larger network in the software market. Kauffman, McAndrews, and Wang (2000) examine how prior investments in proprietary networking technology influence incentives to adopt a multi-bank electronic network.…”
Section: Switching Costs and Network Effectsmentioning
confidence: 99%